ANALISIS FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - sri wahyuti; Putri Cahyani; Abdul Hanafi (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
The aim of this research is to determine and analyze the factors that influence the capital structure of manufacturing companies listed on the Indonesia Stock Exchange. The research method used is a quantitative method, while the sample in this study used purposive sampling with predetermined criteria. This research uses an analytical technique that uses multiple linear regression analysis with the help of the SPSS version 23 computer program to determine the factors that have an influence and relationship on capital structure. The factors that influence the capital structure in this research are in terms of profits, assets and liabilities of the company. The results of the analysis in this study, Return On Equity has an effect on Capital Structure, in this study it states that Return On Equity has a positive and insignificant effect on capital structure, so H1 is rejected. Current Ratio has an effect on Capital Structure, in this research it is stated that Current Ratio has a negative and insignificant effect on capital structure, so H2 is rejected. Debt to Asset Ratio has an effect on Capital Structure, in this research it is stated that Debt to Asset Ratio has a positive and significant effect on capital structure, so H3 is accepted. Overall, ROE, DAR and CR are factors that influence capital structure